Instrumentation, measurements, and experiments in fluids - Rathakrishnan, Ethirajan (Boca Raton, FL : CRC Press, 2019)
Instrumentation, Measurements, and Experiments in Fluids, Second Edition is primarily focused on essentials required for experimentation in fluids, explaining basic principles, and addressing the tools and methods needed for advanced experimentation. It also provides insight into the vital topics and issues associated with the devices and instruments used for fluid mechanics and gas dynamics experiments. The second edition adds exercise problems with answers, along with PIV systems of flow visualization, water flow channel for flow visualization, and pictures with Schlieren and shadowgraph -- from which possible quantitative information can be extracted. Ancillary materials include detailed solutions manual and lecture slides for the instructors.
Need and Objective of Experimental Study. Fundamentals of Fluid Mechanics. Wind Tunnels. Flow Visualisation. Hot-Wire Anemometry. Analogue Methods. Pressure Measurement Techniques. Velocity Measurement. Temperature Measurement. Measurement of Wall Shear Stress. Mass and Volume Flow Measurements. Special flows. Data Acquisition and Processing. Uncertainity.
OCLC-licensed vendor bibliographic record.
Keywords: Fluid mechanics; Fluid dynamic measurements; Fluid mechanics -- Measurement; Fluid mechanics -- Experiments